8(4-2x)=4(3-5x)4x

Simple and best practice solution for 8(4-2x)=4(3-5x)4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(4-2x)=4(3-5x)4x equation:



8(4-2x)=4(3-5x)4x
We move all terms to the left:
8(4-2x)-(4(3-5x)4x)=0
We add all the numbers together, and all the variables
8(-2x+4)-(4(-5x+3)4x)=0
We multiply parentheses
-16x-(4(-5x+3)4x)+32=0
We calculate terms in parentheses: -(4(-5x+3)4x), so:
4(-5x+3)4x
We multiply parentheses
-80x^2+48x
Back to the equation:
-(-80x^2+48x)
We get rid of parentheses
80x^2-48x-16x+32=0
We add all the numbers together, and all the variables
80x^2-64x+32=0
a = 80; b = -64; c = +32;
Δ = b2-4ac
Δ = -642-4·80·32
Δ = -6144
Delta is less than zero, so there is no solution for the equation

See similar equations:

| −5(3x−5)=2(x−31)−117 | | 12(x−48)=3+5x | | z-1/6=2/9 | | 3x-12=42.x | | 4^x-1=8^2x-3 | | g=35-6 | | b^2-13b+22=0 | | 9/k=1 | | 23+3x=3(−x+4)−25 | | 36x=182 | | -3d-10=-37 | | 26=5a+21 | | -5(z+1)=-2z+10−5 | | 7=q–7 | | 70-s=40 | | 3w+3+19w=7w+18 | | 90=6(y+1) | | 7y=3y-36 | | 9+m=23 | | 230=10(-5x+3) | | n/7+8=15 | | 14=21-h | | 4x-5=-3+11 | | -3g+3=9 | | (8x-1)=(10x+5) | | 2(-3x-2)-4x+1=9 | | 90-s=32 | | k-16=21 | | 4x+1=7x−5 | | t/1.5=-5.2 | | 4p+25=209 | | (7x+8)=(10x+5) |

Equations solver categories